Rewatching Content on Streaming Platforms: The Pursuit of Ontological Comfort - Ignacio Siles; Rodrigo Muñoz-González; Luciana Valerio-Alfaro; Vanessa Valiati (Media and Communication)
Why do people tend to rewatch series and films when they have numerous new options at their disposal? This article develops the notion of rewatching on streaming platforms as an essential and enduring aspect of televisuality. Our analysis draws from diary reports completed during one month by 40 streaming platform users in Costa Rica, as well as focus group conversations with 13 of these participants. We examine rewatching as a pursuit of ontological comfort, that is, the sense of well-being derived from people’s understanding of everyday life and their conscious capacity to act in it. We argue that rewatching expresses an active search for stability, predictability, and orchestrated surprise through the narratives and conventions of certain televisual genres and the self-schedule affordances of streaming platforms. This study thus examines the nuanced significance of rewatching and its fundamental connection to the notion of comfort.